2021
DOI: 10.3390/nano11123447
|View full text |Cite
|
Sign up to set email alerts
|

Perfect Optical Absorbers by All-Dielectric Photonic Crystal/Metal Heterostructures Due to Optical Tamm State

Abstract: In this study, we theoretically and experimentally investigated the perfect optical absorptance of a photonic heterostructure composed of a truncated all-dielectric photonic crystal (PC) and a thick metal film in the visible regions. The three simulated structures could achieve narrow-band perfect optical absorption at wavelengths of 500 nm, 600 nm, and 700 nm, respectively. Based on the measured experimental results, the three experimental structures achieved over 90% absorption at wavelengths of 489 nm, 604 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Liu et al [126] have theoretically and experimentally demonstrated single and multi-band near perfect absorber by using simple metal and a 1D PC based structure. Perfect absorbers for visible region are observed in a simple photonic heterostructures composed of a truncated all-dielectric photonic crystal and thick metal film [127] whose schematic is shown in Fig. 10(a).…”
Section: Perfect Absorbersmentioning
confidence: 99%
“…Liu et al [126] have theoretically and experimentally demonstrated single and multi-band near perfect absorber by using simple metal and a 1D PC based structure. Perfect absorbers for visible region are observed in a simple photonic heterostructures composed of a truncated all-dielectric photonic crystal and thick metal film [127] whose schematic is shown in Fig. 10(a).…”
Section: Perfect Absorbersmentioning
confidence: 99%
“…In order to overcome these limitations, a special type of surface polariton state, known as Tamm plasmon-polariton (TPP), was recently proposed [47] and experimentally demonstrated in 2008 by Sasin et al [48] This surface wave is the optical analog of the electronic Tamm states that form on the surface of a crystalline material due to the breaking of its translational symmetry. [49] In recent times, photonic TPP structures have been utilized for the demonstration of tunable perfect absorbers for vis-NIR wavelengths, [50][51][52][53][54] Tamm lasers with tailored emission properties, [55][56][57] thermal emitters, [58,59] temperature sensors, [60][61][62] and real time chemical/bio sensors. [63][64][65][66] Photonic TPP structures are composed of a distributed Bragg reflector (DBR) terminated by a thin metal film.…”
Section: Enhanced Nonlinear Response Of Tamm Plasmon-polariton Struct...mentioning
confidence: 99%
“…Various optical absorbers have been developed in recent years based on PhCs have been reported, most of which are based on all-dielectric PhC structures. For example, an absorber utilizing an all-dielectric PhC structure and a metallic substrate utilizing the optical Tamm state (OTS) was reported by Lu et al [29]. The absorber shows high absorption of 90% in the visible region.…”
Section: Introductionmentioning
confidence: 99%